2015
DOI: 10.1007/s10653-015-9714-z
|View full text |Cite
|
Sign up to set email alerts
|

Formation of dimethyldithioarsinic acid in a simulated landfill leachate in relation to hydrosulfide concentration

Abstract: Dimethyldithioarsinic acid (DMDTA(V)), present in such intense sources as municipal landfill leachate, has drawn a great deal of attention due to its abundant occurrence and different aspect of toxicity. The hydrosulfide (HS(-)) concentration in leachate was studied as a major variable affecting the formation of DMDTA(V). To this end, the HPLC-ICPMS system equipped with the reversed-phase C18 column was used to determine DMDTA(V). Simulated landfill leachates (SLLs) were prepared to cover a mature landfill con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Thus, microbial action can increase both the concentration of methylated As species by methylation from inorganic species and the sulfide concentration by sulfate reduction, 25 causing a rise in reaction rate. An et al 26 confirmed the chemical formation of DMDTA V in simulated landfill leachate and the relationship with sulfide. Landfill leachates under anaerobic conditions show high organic material concentrations containing carboxylic acids as major constituents.…”
Section: ■ Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Thus, microbial action can increase both the concentration of methylated As species by methylation from inorganic species and the sulfide concentration by sulfate reduction, 25 causing a rise in reaction rate. An et al 26 confirmed the chemical formation of DMDTA V in simulated landfill leachate and the relationship with sulfide. Landfill leachates under anaerobic conditions show high organic material concentrations containing carboxylic acids as major constituents.…”
Section: ■ Discussionmentioning
confidence: 88%
“…An et al confirmed the chemical formation of DMDTA V in simulated landfill leachate and the relationship with sulfide. Landfill leachates under anaerobic conditions show high organic material concentrations containing carboxylic acids as major constituents .…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Species included in the stock solutions of DMMTA V and DMDTA V should be examined prior to every analysis, although this protocol suggests storage conditions of 4 ˚C in the dark, which maintains synthesized DMMTA V and DMDTA V with, respectively, 2.2% and 5.8% transformation during the 13 weeks of analysis (Figure 2). , and minor fragments m/z measured by ESI-MS was reproduced from literature 5,13,14,17,19,20,21,22,23,24 . Note that m/z peaks may vary with instrumental conditions and/or matrices of the stock solutions.…”
Section: Representative Resultsmentioning
confidence: 99%